Urgensi Pengaturan Hybrid Contract dalam Pengalihan Utang (Take Over) Untuk Mewujudkan Kepastian dan Keadilan Hukum - Setyawan, David Novan (Law, Development and Justice Review, 2026)
Debt transfer (take over) in contemporary financing practices is increasingly conducted through a hybrid contract structure, which has not been explicitly regulated in statutory law. This condition potentially generates legal uncertainty and injustice for the parties involved, particularly debtors. Therefore, this study examines the urgency of regulating hybrid contracts in debt transfer mechanisms in order to ensure legal certainty and justice. This research employs a normative legal research method with statutory, conceptual, and systematic approaches. These approaches are used to assess the conformity of hybrid contract practices with the principles of contract law and the prevailing positive legal norms in Indonesia. The findings indicate that the absence of specific regulation on hybrid contracts in debt transfer results in normative fragmentation between general civil law, financing law, and modern contractual practices. Such fragmentation leads to ambiguity regarding the legal basis of agreements and weakens legal certainty. Furthermore, this study reveals a normative vacuum concerning the legal standing of hybrid contracts in debt transfer (take over) within the Indonesian civil law system. In practice, take over transactions cannot be purely classified as novation, subrogation, or assignment (cessie), but rather constitute a mixed contractual arrangement that has not been explicitly recognized under positive law. This condition creates ambiguity in determining the applicable legal regime, which in turn affects the validity of agreements and the continuity of collateral. Accordingly, this study underscores the urgency of formulating a normative regulatory framework for hybrid contracts that clearly defines their legal status, stipulates the legal consequences for both principal and accessory obligations, and ensures legal certainty and protection for the parties, particularly debtors.